2013
DOI: 10.1038/ja.2013.72
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide study of Escherichia coli producing extended-spectrum β-lactamases TEM, SHV and CTX-M in Turkey

Abstract: Four hundred and forty extended-spectrum β-lactamase (ESBL)-producing Escherichia coli isolates were collected from 10 different hospitals in Turkey between 2011 and 2012. Clinical specimens consisted of urine (80.45%), blood (6.59%), cerebrospinal fluid (1.13%), pleural fluid (2.95%), wound (4.31%) and sputum (4.54%). ESBL-coding genes (CTX-M1, CTX-M2, TEM, SHV) were detected by PCR. According to the PCR and sequencing results, CTX-M1 was the most prevalent β-lactamase 83.18% (366/440), followed by TEM 44.09%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 19 publications
0
6
2
Order By: Relevance
“…CTX-M-15 dominates in Germany and the Netherlands, but more recent studies show an increased proportion of CTX-M-1 compared to CTX-M-14 (Voets et al, 2012; Pietsch et al, 2017). CTX-M-14 has been found to be less prevalent in most countries with some exceptions [China, South-East Asia, South Korea, Japan, and Spain; (Onnberg et al, 2011; Copur Cicek et al, 2013; Helldal et al, 2013; Bevan et al, 2017)]. Although we found CTX-M-14 in all investigated countries it was less prevalent than CTX-M-15.…”
Section: Discussioncontrasting
confidence: 66%
“…CTX-M-15 dominates in Germany and the Netherlands, but more recent studies show an increased proportion of CTX-M-1 compared to CTX-M-14 (Voets et al, 2012; Pietsch et al, 2017). CTX-M-14 has been found to be less prevalent in most countries with some exceptions [China, South-East Asia, South Korea, Japan, and Spain; (Onnberg et al, 2011; Copur Cicek et al, 2013; Helldal et al, 2013; Bevan et al, 2017)]. Although we found CTX-M-14 in all investigated countries it was less prevalent than CTX-M-15.…”
Section: Discussioncontrasting
confidence: 66%
“…Previously, the rates of bla SHV containing Enterobacterales with a focus on uropathogenic isolates were reported 12.2% to 54.8% by Iranian authors. [24][25][26][27][28][29] Meanwhile, several authors have shown the global spared of SHV type β-lactamases in uro- pathogenic Enterobacterales from China, 30 India, 31 Saudi Arabia, 32 Turkey, 33 Ukraine, 34 and Morocco. 35 In our results, 4.1% of uropathogenic Enterobacterales contained bla NDM-1, which to the best of our knowledge, is the first prevalence of this gene in Guilan province (North of Iran).…”
Section: Discussionmentioning
confidence: 99%
“…CTX-M-15 were reported in healthy dogs by several studies [17, 24, 34, 41, 54]. CTX-M-15 is also the most commonly reported enzyme type in E. coli isolates from human clinical samples [2, 13, 19]. Recent studies in Turkey shows presence of this enzyme among ESBL producing E. coli isolates in cattle and retail meat [3, 37].…”
Section: Discussionmentioning
confidence: 99%